Quality Improvement in Increasing Public Trust Using the Failure Mode and Effect Analysis (FMEA) Method - Hasan Baharun; Rizkiyah Hasanah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This article discusses quality improvement in increasing public trust in MI Ihyauddiniyah. This study used a qualitative case study approach, with the research subjects consisting of the school principal and several deputy heads. Data collection techniques using interviews, documentation, and observation. Data analysis techniques using data reduction, data presentation, and concluding. This research focuses on describing quality improvement in increasing public trust using the Failure Mode and Effect Analysis (FMEA) method of researchers at MI Ihyauddiniyah. The research data was obtained through interviews and observation, and documentation. In the next stage, the researcher checked the validity of the data, which was carried out by extending participation, persistence in observation, triangulation, and questionnaires to parents of students. To get more accurate and accountable results, the researchers interviewed the deputy head of student affairs, deputy head of infrastructure, and teachers at MI Ihyauddiniyah. The results showed that quality improvement using the FMEA method increased public trust. The FMEA measurement process is focused on three main things, which are the main components in the management process of educational institutions. The three components are a quality assurance system for teaching staff, a quality assurance system for learning facilities and infrastructure, and increasing support from the community, through this process.